PENGARUH KOMPETENSI DAN PENGEMBANGAN KARIER TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN KEPEGAWAIAN, PENDIDIKAN DAN PELATIHAN DAERAH KABUPATEN SIDENRENG RAPPANG - Andi Batary Citta; Arfiany Arfiany (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2019)
AbstractsThe purpose of this study was to determine the effect of competence and career development on employee performance. The population in this study were employees of the agency, education and training office. The sampling technique uses Stratified Random Sampling and obtained a sample of 36 respondents. This research variable uses two variables, namely the dependent and independent variables. For the dependent variable (y) of this study is employee performance. For independent variables (x) include: competence (x1), and career development (x2). Quantitative data analysis method, using multiple linear regression analysis models. Bring it to process data using the SPSS 23 program. The results of this study indicate that partially positive and significant effect of the competency variable gives an effect of 3,880 on employee performance, and from career development variables has an influence of 2,467 on employee performance. Keywords: Competence, Career Development, and Employee Performance.